Morphological results of customized microvascular mandibular reconstruction: A comparative study. Issue 6 (June 2016) - Tarsitano, Achille; Ciocca, Leonardo; Scotti, Roberto; Marchetti, Claudio
Abstract: Introduction: Virtual planning and guided surgery with customized reconstructive plates are becoming more and more common for mandibular reconstruction with fibular free flaps. Although the literature describes many potential applications, no systematic analyses have been made about morphological results regarding computer-aided reconstruction compared to traditional freehand bent plate. Materials and methods: In the present study, we propose a comparative study in this innovative field, analysing a case series of 30 CAD/CAM reconstructed mandibles, compared to traditional reconstructed mandibles, in terms of morphological results. All patients were evaluated by pre-operative and a post-operative CT scan. To evaluate the morphological results, several anatomical landmarks were measured on CT scan: 1) the midline deviation; 2) the amplitude variation, in grades, of the mandibular angle; 3) the bi-gonial diameter of the mandibular and 4) the chin protrusion. Results: The mean differences registered between pre-operative and post-operative CT scan were significantly better for test group regarding mandibular angle (p = 0.034), bi-gonial diameter (p = 0.041), chin protrusion (p = 0.05). No significant differences were registered for midline deviation (p = 0.092). Conclusion: CAD/CAM reconstructive technique appears to be a valid method to accurately restore the pre-operative morphological situation.